Building Scalable Enterprise Systems: The Intersection of Web Technology, Cloud Computing, and AI Marketing - Ahmed Shaban, Awaz; R. M. Zeebaree, Subhi (Polaris Global Journal of Scholarly Research and Trends, 2025)
The rapid evolution of digital technologies has transformed enterprise scalability, necessitating the integration of cloud computing, artificial intelligence (AI), and web technologies. Traditional enterprise architectures often struggle with dynamic workloads, operational efficiency, and adaptability to market demands. This study explores the intersection of web technology, cloud computing, and AI-driven automation in building scalable enterprise systems. Through an extensive literature review, comparative analysis, and extracted industry statistics, this research identifies key strategies such as hybrid and multi-cloud adoption, microservices-based architectures, AI-driven decision-making, and Zero Trust security frameworks. The findings highlight the importance of API-first architectures, predictive analytics, and automated cloud resource management in achieving business agility and cost optimization. Additionally, the study discusses the challenges of data security, integration complexity, regulatory compliance, and cost management in implementing scalable enterprise solutions. The research concludes that organizations that effectively implement AI, cloud technologies, and web-based solutions gain a competitive advantage through increased agility, operational efficiency, and digital resilience. Future research should focus on quantum computing, blockchain integration, ethical AI governance, and industry-specific scalability challenges to further enhance enterprise digital transformation efforts.